Development of Differentiated Learning Models for Scientific Writing Skills in Higher Education - Mazhud, Nurfathana; Hamsa, Akmal; Mantasiah R (International Humanity Advance, Business & Sciences, 2025)
The mastery of scientific writing is a critical academic competence for university students, yet conventional instructional approaches often fail to address the diverse learning needs within higher education settings. This study aims to develop a differentiated learning model tailored to enhance students’ scientific writing skills. Employing a design-based research methodology, the model was iteratively tested and refined in undergraduate classrooms. The findings indicate that differentiated instruction by accommodating students’ readiness levels, learning preferences, and interests significantly improves engagement, self-efficacy, and the quality of academic writing. The study contributes to pedagogical innovation by offering a structured and adaptable framework for writing instruction in diverse academic environments.